Non-invasive monitoring of cyanobacteria growth in a nanocellulose matrix - Levä Tuukka; Mahlamäki Ella; Kosourov Sergey; Allahverdiyeva Yagut; Mäkelä Mikko; Tammelin Tekla (Elsevier BV, 2025)
Solid-state photosynthetic cell factories (SSPCFs) for sustainable chemicals manufacturing can be developed towards industrially relevant environment with rapid feedback control over their operation. This requires non-invasive monitoring of the immobilized cells in situ, which is not possible with existing methods. We deployed hyperspectral imaging in the photosynthetically active radiation range (400–700 nm) to enable such monitoring. We systematically assessed cell growth and potential stress during immobilization by studying how 2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPO)-oxidized cellulose nanofiber hydrogel thickness, immobilized Synechocystis sp. PCC 6803 cell density and time affected the immobilized cells' absorbance spectra. Time and gel thickness together accounted for almost 80 % of the changes in the spectra. We then calibrated the imaging spectra for chlorophyll a to non-invasively estimate growth of healthy cells in the matrices. Promising correlation for chlorophyll a (model coefficient of determination, R2 = 0.90) was observed between hyperspectral imaging and spectrophotometry references from methanol-extracted samples regardless of spatial differences that developed in the matrices over time. Clustering of the image pixels enabled analyzing these differences in the chlorophyll a concentration non-invasively from the whole matrix areas. In the future, this non-invasive data-driven method could be further developed for monitoring SSPCFs' biointelligent chemicals production, contamination, stress and cell growth.